Suicidal behavior in students of the School of Social Work at the Universidad Nacional Mayor de San Marcos - Perales, Alberto (2012)
In 2010, Perales et al. found in medical students of the Universidad Nacional Mayor de San Marcos a lifetime prevalence of suicide attempts than 4%. The purpose of this study is to estimate the prevalence of this problem among students from the School of Social Work at the university, as there are no data on the country. To estimate the prevalence of suicidal behavior and associated factors in students of the School of Social Work at San Marcos. METHODS: Cross-sectional analytical study on the universe of students enrolled in the School of Social Work in 2011. In group sessions, were applied measuring instruments (scales of self-measurement of depression and anxiety Zung, guest suicidal, homicidal thoughts and indicators of antisocial behavior and CAGE) students who previously gave written informed consent. Data were subjected to descriptive and specific analysis of key survey variables.